Pemanfaatan Gadget dalam Proses Pembelajaran Pendidikan Agama Islam di SDN 01 Sidoharjo Jati Agung Lampung Selatan - Anisa Isti Qomah; An An Andari; Cipto Handoko (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to analyze in-depth how the use of gadgets in Islamic Religious Education learning at SDN 01 Sidoharjo Jati Agung, South Lampung, is implemented pedagogically and oriented towards the formation of students' religious values. This study used a qualitative approach with a case study to gain an in-depth understanding of the use of gadgets in Islamic Religious Education learning at SDN 01 Sidoharjo Jati Agung, South Lampung. The location and subjects were selected purposively, including Islamic Religious Education teachers, the principal, and students. Data were collected through participant observation, semi-structured interviews, and documentation of digital learning materials. Data analysis was conducted thematically using triangulation techniques to ensure credibility. This study yielded a contextual understanding of gadget use strategies and their implications for learning and internalizing religious values. This study concluded that the use of gadgets in Islamic Religious Education learning at SDN 01 Sidoharjo Jati Agung, South Lampung, plays a strategic role in increasing learning effectiveness. Gadgets are used as contextual and visual media, presenting videos of prophetic stories, moral animations, and illustrations that help students understand religious concepts in depth and encourage value reflection. Furthermore, gadgets enhance student active engagement through participation, discussion, and critical inquiry, creating interactive and dialogic learning. Gadget use is also geared toward supporting the internalization of religious and moral values ??through relevant digital content and reflective reinforcement by teachers. Overall, gadgets are an effective pedagogical strategy for meaningful, participatory, and student-centered Islamic Religious Education (PAI) learning.